Saudi Israeli Relations: The Benefits and Implications of an Alliance - Altaf, Amani; David, Steven (Journal of Student Research, 2023)
As the power dynamics in the Middle East change, with Iran gaining power and influence, relations between Saudi Arabia and Israel are changing as well. While previously in an antagonistic relationship, the two countries would benefit from developing an alliance. However, the cultural and social implications, especially in terms of Israel’s occupation of Jerusalem and the Islamic significance of the city, must be considered. Despite these reservations, an alliance could prove beneficial as Saudi Arabia could encourage and move forward with a peace process between Israel and Palestine. In addition, Israel could help improve Saudi Arabia’s defense against Iran – an issue important to both countries – and speed up the economic transformation currently taking place in the country as it moves away from dependence on oil. Given these benefits, and the likelihood that there will be little internal opposition to an alliance, the development of a relationship between Saudi Arabia and Israel would strengthen Saudi Arabia as a country and improve stability in the Middle Eastern region.